Exploring the Effectiveness of Online Tools in Enhancing English Language Learning: Opportunities and Challenges - Wahid, Delfia Herwanis; Zakaria, Rahmanita; Rusmiati, Rusmiati (Buletin Literasi Budaya Sekolah, 2023)
This study examines the effectiveness of online resources in enhancing the process of learning the English language, as well as the opportunities and challenges that come with it. The research findings indicate that students often and regularly use online resources to learn languages. Students universally deemed internet technologies as highly beneficial in augmenting the accessibility of educational materials and resources, emphasizing their substantial importance in contemporary language education. In addition, students expressed favorable results about their practical language competency and the enhancement of their language skills in authentic situations. Most students found it easy to stay motivated and disciplined when using online tools, highlighting the positive impact these resources have on motivation. In summary, this study offers useful insights into the beneficial impact of online tools on the process of learning the English language. It emphasizes the potential of these tools to transform and improve the field of language teaching.